Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing


  • 3 years ago

Show that: L (\sigma\ i=1 to M c(n)*u(n)) = \sigma\ i=1 to M c(n)L(u(n))

  • This Question is Open
  1. UnkleRhaukus
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    \[L \left(\sum\limits_{i=1}^ M c(n)*u(n)\right) = \sum\limits_{ i=1}^M c(n)L\big(u(n)\big)\]? what does the L mean ?

  2. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy